(untitled) (Fiep Bulletin - online, 2015)
This study aims at developing some reflections on a worldwide epidemic and a major challenge to healthcare systems, i.e. Diabetes. It seeks to demonstrate gains for students with Diabetes Mellitus Type 1 derived from a regular practice of physical activities. Those gains would be detectable not only in the maintenance of blood glucose and lipid profile rates at desirable levels, but would also enable conditions for the accomplishment of some recommendations for the promotion of a healthy lifestyle in school. Moderate physical activities are aimed at reducing the risk of opportunistic infections in children with this diagnosis, and also at preventing other associated risk factors: sedentary life, obesity, and hypertension. Well planned exercises and a balanced diet favor the control of this chronic disease, and also increase the muscular glucose capacity, energy use, reduction of cholesterol and triglyceride rate levels, decrease in blood pressure and a feeling of well being and social inclusion. Previous studies carried out by Miculis and collaborators (2010) found out that many children with DM1 still keep a level of sports or recreational practice lower than recommended. In addition, many schools still practice restrictions against DM1 children’s participation in physical activities at school, only allowing those practices in the presence of a parent or legal guardian.